Kepesertaan Keluarga Berencana Pada Masa Awal Pandemi Covid-19 Di Daerah Istimewa Yogyakarta - Witono Witono; Suparna Parwodiwiyono (Perwakilan BKKBN Daerah Istimewa Yogyakarta, 2020)
The Covid-19 pandemic has affected the family planning (KB) participation. This paper aims to determine the development of family planning participation in the Special Region of Yogyakarta, especially those related to the use of contraceptive methods in the early days of the Covid-19 pandemic, in March-April 2020.. The data were sourced from the results of the Monthly Field Family Planning Participation Control Report and Contraception Services Report in BKKBN Yogyakarta Special Region in January-April 2020. The results show that the number of active and new contraceptive prevalence in the early Covid-19 pandemic experienced a decline, while unmet need for contraception showed a tendency to increase in the same period. The number of new family planning participants appears to have decreased in March-April 2020 along with the addition of the number of positive cases of Covid-19 in the Special Region of Yogyakarta. This is due to the decrease in the intensity of family planning counseling and services.